3D Quantitative Evaluation of Posture and Spine Proprioceptive Perception Through Instinctive Self-Correction Maneuver in Adolescent Idiopathic Scoliosis - Kinel, Edyta; D’Amico, Moreno; Roncoletta, Piero (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Conservative treatment in the adolescent idiopathic scoliosis (AIS) population is based on individual proprioceptive and motor control training. Such training includes physiotherapeutic scoliosis-specific exercises (PSSEs) stimulating the individual capacity to perceive and control his/her posture, particularly the shape of the spine. However, limited knowledge about basic proprioception capability in AIS patients is reported in the literature. Questions: 1) How AIS patients, who did not receive any previous specific postural education treatment, perceive their posture and 3D spine shape? Are they able to modify their posture and 3D spine shape correctly through an instinctive self-correction (ISCO) manoeuvre? 2) Are posture and ISCO manoeuvre ability gender dependent in AIS patients? 3) Do AIS patients present different posture and spine shape characteristics as well as different ISCO ability compared to the healthy young adult population? Methods: Cross-sectional observational study. 132 (75 females, 57 males) AIS patients’ posture and 3D spine shape have been measured comparing Indifferent Orthostasis (IO) (neutral erect posture) to ISCO using a non-ionising 3D optoelectronic stereophotogrammetric approach. Thirteen quantitative biomechanical parameters described the AIS patients body posture. The statistical analysis was performed using a multivariate approach to compare genders in IO, ISCO, and AIS patients vs healthy young adults-previously-published data (57 females, 64 males). Results: 87.7% (males) and 93.3% (females) of AIS patients were unable to modify posture and 3D spine shape globally. AIS patients gender differences were found in IO, ISCO and the comparison vs healthy young adults. When changes occurred, subjects could not focus and control their posture globally, but only in a few aspects at a time. Conclusions: Self-correction manoeuvre producing an improvement in body posture and spine shape is not instinctive and must be trained. In such characteristics, AIS patients are not so dissimilar to healthy young adults. Sagittal plane control is the highest, but ISCO in AIS patients led to worsening in this plane. Control at the lumbar level is neglected in both genders. Such outcomes support the necessity of customised PSSEs to treat AIS patients. The 3D stereo-photogrammetric approach is effective in quantitatively describing the subject’s posture, motor control and proprioception.